Hepatic gene therapy rescues high-fat diet responses in circadian Clock mutant mice - Judit Meyer-Kovac; Isa Kolbe; Lea Ehrhardt; Alexei Leliavski; Jana Husse; Gabriela Salinas; Thomas Lingner; Anthony H. Tsang; Johanna L. Barclay; Henrik Oster (Elsevier, 2017)
Objective: Circadian Clock gene mutant mice show dampened 24-h feeding rhythms and an increased sensitivity to high-fat diet (HFD) feeding. Restricting HFD access to the dark phase counteracts its obesogenic effect in wild-type mice. The extent to which altered feeding rhythms are causative for the obesogenic phenotype of Clock mutant mice, however, remains unknown. Methods: Metabolic parameters of wild-type (WT) and ClockΔ19 mutant mice (MT) were investigated under ad libitum and nighttime restricted HFD feeding. Liver circadian clock function was partially rescued by hydrodynamic tail vein delivery of WT-Clock DNA vectors in mutant mice and transcriptional, metabolic, endocrine and behavioral rhythms studied. Results: Nighttime-restricted feeding restored food intake, but not body weight regulation in MT mice under HFD, suggesting Clock-dependent metabolic dysregulation downstream of circadian appetite control. Liver-directed Clock gene therapy partially restored liver circadian oscillator function and transcriptome regulation without affecting centrally controlled circadian behaviors. Under HFD, MT mice with partially restored liver clock function (MT-LR) showed normalized body weight gain, rescued 24-h food intake rhythms, and WT-like energy expenditure. This was associated with decreased nighttime leptin and daytime ghrelin levels, reduced hepatic lipid accumulation, and improved glucose tolerance. Transcriptome analysis revealed that hepatic Clock rescue in MT mice affected a range of metabolic pathways. Conclusion: Liver Clock gene therapy improves resistance against HFD-induced metabolic impairments in mice with circadian clock disruption. Restoring or stabilizing liver clock function might be a promising target for therapeutic interventions in obesity and metabolic disorders. Keywords: Circadian clock, Clock gene, High-fat diet, Liver, Transcription, Gene therapy